2018
DOI: 10.4172/2329-9495.1000210
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness in Patients with Diabetes Mellitus Attending Tertiary Care Hospital in Nigeria

Abstract: Objective: Carotid intima-media thickness is a significant and independent predictor of coronary artery disease in patients with diabetes. The aim of our study was to determine carotid intima-media thickness in Nigerians with diabetes. Methods:This was an observational cross-sectional study involving consecutively presenting patients with type 2 diabetes mellitus and healthy age-matched adults. Anthropometric variables were measured, and blood samples collected for fasting blood sugar, cholesterol, and HbA1c. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These findings are statistically significant in both groups (p=0.000 and p=0.019). This finding is in agreement with the previous studies (Hassan et al, 2016;Baba et al, 2018). The possible reason for such variations between right and left CCIMT is not yet clear.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are statistically significant in both groups (p=0.000 and p=0.019). This finding is in agreement with the previous studies (Hassan et al, 2016;Baba et al, 2018). The possible reason for such variations between right and left CCIMT is not yet clear.…”
Section: Discussionsupporting
confidence: 92%
“…This prevalence is significantly lower when compared to similar studies such as Baba et al in which the diabetic group had a significantly higher mean CIMT compared to control at all levels. Seventy-nine (90.8%) of the patients with diabetes in this particular study had CIMT greater than 0.9 mm, while sixty-nine (79.3%) had CIMT greater than 1.0 mm [30] . This discrepancy in prevalence size may be due to inclusion of hypertensive patients, patients with elevated cholesterol which resulted in a broader sample size as opposed to this study which excluded patients with elevated blood pressure, stroke, elevated cholesterol levels resulting in a much smaller sample size which in turn resulted in a smaller prevalence.…”
Section: Discussionmentioning
confidence: 60%
“…Carotid intima-media thickness and plaque: the mean CIMT in this study was similarly reported by Baba et al . [ 31 ]. However, its value is higher than that reported in Turkey [ 32 ] and lower than the controls of Koc et al .…”
Section: Discussionmentioning
confidence: 99%
“…The CIMT at the CB being significantly higher than the CCA and ICA as similarly reported by Baba et al . [ 31 ] may be due to anatomy at carotid artery bifurcation and resultant hemodynamic changes [ 34 ]. The increased CIMT observed in our study participants was lower than 53.7% and 36.5% reported by Omisore et al .…”
Section: Discussionmentioning
confidence: 99%